PENGARUH PENGETAHUAN PERPAJAKAN DAN KEPATUHAN PADA USAHA KECIL DAN MENENGAH (UKM) TERHADAP KEWAJIBAN PERPAJAKAN - Heri Heri; Henni Rahayu Handayani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study was to determine the effect of Tax Knowledge and Compliance on Small and Medium Enterprises (SMEs) on Tax Obligations. The variables that become the focus of this research are Tax Knowledge and Compliance (X) as independent variables and Tax Obligations (Y) as dependent variable. The type of research used in this research is quantitative. The population used is Small and Medium Business Taxpayers (UKM) in South Tangerang City, totaling 11,287 respondents. The sampling technique is the Slovin formula with a sample of 386 respondents obtained from Small and Medium Enterprise Taxpayers (SMEs) in South Tangerang City. Data analysis using Validity Test, Reliability Test, Data Normality Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Coefficient of Determination (KD), Multiple Linear Regression Analysis, Hypothesis Testing (T test) and (F test), then the calculation uses the SPSS program version 22. The results of the analysis and discussion show that partially Tax Knowledge has a positive and significant effect on Tax Obligations, Compliance has a positive effect on Tax Obligations. Simultaneously on Small and Medium Business Taxpayers (SMEs) in South Tangerang City. This means that there is a significant positive influence simultaneously between Tax Knowledge and Compliance with Tax Obligations.